Overlapping Inequalities in the Welfare State Strengths and Challenges of Intersectionality Framework - Akkan, Başak; Hahmann, Julia; Hunner-Kreisel, Christine; Kuhn, Melanie (Springer International Publishing : Imprint: Springer, 2024)
XII, 394 p. 3 illus., 2 illus. in color.